Oral Contraceptive and Glioma Risk: A Prospective Cohort Study and Meta-Analysis - Shao, Chuan; Tang, Hui; Wang, Xiaoya; He, Jiaquan; Wang, Pan; Wu, Nan (Frontiers in Public Health, 2022)
Background: Epidemiological evidence that glioma has a slight male predominance implies that factors associated with sex hormones may play a role in the development of glioma. The association between oral contraceptive (OC) use and glioma risk remains controversial. Method: In the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial of 70,516 women in the USA, Cox proportional hazards regression analyses were adopted to calculate the crude and adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). Additionally, a meta-analysis combining the PLCO findings with those of other prospective cohorts was performed. Results: During a mean follow-up of approximately 11.7 years, 110 of 70,516 women aged 50–78 years at baseline were diagnosed with glioma in PLCO studies. Compared with never users, an inverse association of borderline significance was found for OC users (HR 0.67, 95% CI 0.44–1.04, P=0.074). Analyses assessing glioma risk according to the duration of OC use yielded no significant association. When PLCO was combined with four other prospective studies, there was an inverse association between OC use and glioma risk (HR 0.85, 95% CI 0.75–0.97, I2=0.0%). Further dose-response analysis showed a nonlinear, inverse relationship between OC use and glioma risk (P<0.001). Conclusions: This study provided some evidence of a nonlinear, inverse association between OC use and glioma risk. Future larger studies are warranted to validate this finding.